Design of mini conveyor using a mechanical (Geneva) mechanism / Muhammad Syafiq Qayyum Salehuddin - Salehuddin, Muhammad Syafiq Qayyum (2023)
Geneva mechanism is a system to convert continuous circular motion into fixed step circular motion. This simple Geneva mechanism consists of a drive wheel and a driven wheel. This Geneva mechanism converts continuous rotation of the drive wheel into intermittent rotation of the gear. This mechanism using belt conveyor which is made up of rubber have basic function of transporting material in process of manufacturing. In addition, there are several types of Geneva rotator which is external Geneva rotator, internal Geneva rotator and spherical Geneva rotator. For this project that used conveyer belt is an external Geneva rotator. This mechanism produces jerks or instantaneous in acceleration. This mechanism has been used in many applications. For example, film projectors used this mechanism to power a motor which is used for fast forward. It is one of the most simple and inexpensive mechanisms.